Heterologous Expression of PKPI and Pin1 Proteinase Inhibitors Enhances Plant Fitness and Broad-Spectrum Resistance to Biotic Threats - Turrà, David; Vitale, Stefania; Marra, Roberta; Woo, Sheridan L.; Lorito, Matteo (Frontiers in Plant Science, 2020)
Kunitz-type (PKPI) and Potato type I (Pin1) protease inhibitors (PIs) are two families of serine proteinase inhibitors often associated to plant storage organs and with well known insecticidal and nematicidal activities. Noteworthy, their ability to limit fungal and bacterial pathogenesis in vivo or to influence plant physiology has not been investigated in detail. To this aim, we generated a set of PVX-based viral constructs to transiently and heterologously express two potato PKPI (PKI1, PKI2) and three potato Pin1 (PPI3A2, PPI3B2, PPI2C4) genes in Nicotiana benthamiana plants, a widely used model for plant-pathogen interaction studies. Interestingly, transgenic plants expressing most of the tested PIs showed to be highly resistant against two economically important necrotrophic fungal pathogens, Botrytis cinerea and Alternaria alternata. Unexpectedly, overexpression of the PKI2 Kunitz-type or of the PPI2C4 and PPI3A2 Potato type I inhibitor genes also lead to a dramatic reduction in the propagation and symptom development produced by the bacterial pathogen Pseudomonas syringae. We further found that localized expression of PPI2C4 and PKI2 in N. benthamiana leaves caused an increase in cell expansion and proliferation which lead to tissue hypertrophy and trichome accumulation. In line with this, the systemic expression of these proteins resulted in plants with enhanced shoot and root biomass. Collectively, our results indicate that PKPI and Pin1 PIs might represent valuable tools to simultaneously increase plant fitness and broad-spectrum resistance towards phytopathogens.